Religion, globalization and culture - Beaman, Lori G.; Beyer, Peter, 1949- (International Studies in Religion and Society, 2007)
This volume brings together over 25 articles by many of the most important authors who have worked on issues directly related to the theme of religion and globalization. An additional emphasis on culture flags the inclusion of the relation of religion to its wider social context and also permits questioning the boundaries of religion so as to avoid a strong bias in favour of the analysis of institutionalized religion. The key emphasis of the book, however, is the focus specifically on religion, a topic that is still largely ignored in the burgeoning literature on globalization. The articles are divided into five subthemes: theoretical issues; historical approaches to religion and globalization; forms and boundaries of religion; key issues (such as ecology and gender); and regional perspectives. Contributors: Afe Adogame, Elisabeth Arweck, Lori Beaman, Peter Beyer, John Boli, Gary Bouma, Dave Brewington, George Van Campbell, José Casanova, Paul Freston, Nobutaka Inoue, Laurel Kearns, Otto Maduro, Vasilios Makrides, Meredith McGuire, Vincenzo Pace, Rubina Ramji, James T. Richardson, Ole Riis, Roland Robertson, Marie-Andrée Roy, Shandip Saha, John H. Simpson, James V. Spickard, William Stahl, George Thomas, Bryan Turner, Margit Warburg, Michael Wilkinson.